Polarization of free electrons by means of resonance microwave pumping using normal and anomalous doppler effect - Ivanov, B.I. (Вопросы атомной науки и техники, 2001)
The method of electron polarization by pumping the electron spin resonance (ESR), using a running wave with a phase velocity close to the electron beam velocity, is proposed. Repeatedly alternating pumping by the following wave and by the counter wave, it is possible to realize nearly full electron polarization. Similar, and even more effective, this method can make electron polarization using alternation of a normal Doppler effect on the following wave (thus the wave phase velocity exceeds the velocity of the beam) and an anomalous Doppler effect on the following wave too (when, on the contrary, the velocity of the beam exceeds the phase velocity of the wave).